2021
DOI: 10.3389/fonc.2021.723345
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET/CT Radiomics for Preoperative Prediction of Lymph Node Metastases and Nodal Staging in Gastric Cancer

Abstract: ObjectivesThe accurate assessment of lymph node metastases (LNMs) and the preoperative nodal (N) stage are critical for the precise treatment of patients with gastric cancer (GC). The diagnostic performance, however, of current imaging procedures used for this assessment is sub-optimal. Our aim was to investigate the value of preoperative 18F-FDG PET/CT radiomic features to predict LNMs and the N stage.MethodsWe retrospectively collected clinical and 18F-FDG PET/CT imaging data of 185 patients with GC who unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 35 publications
0
27
0
Order By: Relevance
“…A total of 7 studies on gastric cancer were found [ 29 , 30 , 31 , 32 , 33 , 34 , 35 ], all using 18F-FDG as radiopharmaceutical. The average number of patients included was 163.7 (range 79–214), with 5/7 (71.4%) studies including more than 100 patients, 5/7 (71.4%) using a separate validation dataset and 1/7 (14.3%) using prospective data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 7 studies on gastric cancer were found [ 29 , 30 , 31 , 32 , 33 , 34 , 35 ], all using 18F-FDG as radiopharmaceutical. The average number of patients included was 163.7 (range 79–214), with 5/7 (71.4%) studies including more than 100 patients, 5/7 (71.4%) using a separate validation dataset and 1/7 (14.3%) using prospective data.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, 4 studies were conducted for diagnostic purposes: 2 for nodal involvement prediction (AUC between 0.74 and 0.81) [ 29 , 35 ], 1 for peritoneal involvement prediction (AUC 0.88 in the validation cohorts) [ 30 ] and 1 to differentiate between gastric cancer and primary gastric lymphoma (AUC 0.77) [ 31 ]. The remaining three were prognosis-oriented [ 32 , 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Other studies ( 29 31 ) also have shown that the combination of CT anatomical images and PET metabolic images for radiomics analysis is more effective in differential diagnosis and prognosis evaluation of diseases than PET alone, and the accuracy of predicting LNM is significantly better than that of conventional PET/CT diagnosis. Recently, a study using 18 F-FDG PET/CT radiomics features ( 31 ) randomly assigned 185 patients with GC to the training cohort and verification cohort in a ratio of 8:2 and established BalancedBagging ensemble classifier for predicting LNM in GC. Although it has different sample sizes and methodology, the PET/CT-score for predicting LNM preoperatively in the present study is similar to that of the aforementioned study ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study using 18 F-FDG PET/CT radiomics features ( 31 ) randomly assigned 185 patients with GC to the training cohort and verification cohort in a ratio of 8:2 and established BalancedBagging ensemble classifier for predicting LNM in GC. Although it has different sample sizes and methodology, the PET/CT-score for predicting LNM preoperatively in the present study is similar to that of the aforementioned study ( 31 ). In clinical practice, adequate analysis of clinical and imaging data can contribute to the correct diagnosis and management of GC, so we further combined PET/CT radiomics features with clinical risk factors to construct a radiomics nomogram to predict LNM.…”
Section: Discussionmentioning
confidence: 99%
“…In future, a large multicenter cohort study or prospective study with a standardized protocol would be needed to overcome these limitations and to establish reliable volumetric ranges and sums of SA ranges for loco-regional nodal stations in GC. Secondly, measuring every single LN detected at preoperative CT is too time-consuming to be feasible at every center in everyday clinical practice and artificial intelligence could be helpful in this field, since different radiomics models, both in CT and PET/CT images analysis, proved to be effective in prediction of nodal metastases in GC [ 38 , 39 , 40 , 41 ]. Nonetheless, in this study we considered easily-measurable parameters that do not demand specific training for radiologists.…”
Section: Discussionmentioning
confidence: 99%